Climate Variability Drives Watersheds Along a Transporter‐Transformer Continuum. Issue 21 (9th November 2021) - Fazekas, Hannah M.; McDowell, William H.; Shanley, James B.; Wymore, Adam S.
Abstract: We examined how climate variability affects the mobilization of material from six watersheds. We analyzed one to seven years of high‐frequency sensor data from a temperate ecosystem and a tropical rainforest. We applied a windowed analysis to correlate concentration‐discharge (C‐Q) behavior with climate anomalies, providing insight into how hydrological and biogeochemical processes change in response to climate variability. Positive precipitation anomalies homogenized the C‐Q responses for dissolved organic matter, nitrate, specific conductance and turbidity, indicating that hydrological processes dominate the C‐Q signal and watersheds act as "conveyor belts" of material. In contrast, drier and warmer conditions led to C‐Q behavior associated with variation in solute concentration, suggesting that biogeochemical processes are a primary control on solute export and their response to flow. Results indicate that climate variability can move watersheds along a continuum from transporter‐to‐transformer of biologically active solutes and responses can potentially vary by biome. Plain Language Summary: Watersheds transport and transform material as water moves through the landscape to downstream waterbodies. We evaluated how variability in precipitation and temperature affect the movement of solutes and sediment from watersheds to river networks in temperate forests and tropical rainforests by examining the relationships between concentration and flow across six watersheds. We found that during wetter than typical conditions, hydrology dominates the relationship between concentration and discharge and watersheds act as a conveyor belt of material to the stream network. During drier and warmer than typical conditions, we observed high variability in concentration of solutes relative to discharge suggesting that watershed and in‐stream biogeochemical processes are the primary control on solute export. Under these conditions, the stream and watershed acts as a transformer of material. These results indicate that variability in climate can move watersheds and river networks along a continuum from transporter‐to‐transformer of biologically active solutes. Key Points: Watersheds transition along a transporter‐transformer continuum across a range of precipitation anomalies in tropical and temperate biomes Synergistic effects of dry conditions and warming temperatures may affect the export of biologically reactive solutes in temperate systems Higher nitrate flux occurred during negative precipitation anomalies than during the largest positive precipitation anomalies